Doc Martin. Series 8 [videorecording (DVD)] - Clunes, Martin, 1961-; Catz, Caroline; McNeice, Ian; Cadell, Selina; Atkins, Eileen, 1934- (Acorn, 2017)
In these all-new episodes, the doctor continues his practice in the picturesque seaside town of Portwenn, while raising his son with wife Louisa.